Bank Garansi Sebagai Pengalihan Kewajiban Jika Terjadi Wanprestasi Oleh Nasabah BRI KCP Kelapa Gading - Stephanie Priscilla Darmawan (Departement of Mathematics Education, 2023)
The research aims to issue a bank guarantee bank KCP BRI Kelapa Gading so that there is no transfer of obligations due to default. Any default will result in the withdrawal of capital which affects the liquidity of the bank's capital. Concerning collateral, both movable and immovable assets are not easy to sell quickly. If there are many defaults, the bank will lack capital to support banking performance. The lack of defaults maintains bank security so that the banking industry does not quickly collapse and maintains public trust.Normative legal research method, qualitative method approach, the case study of KCP BRI Kelapa Gading. Primary data was obtained directly from research results based on available data. Secondary data include books, journal publications, written laws, and regulations. interview data collection techniques, data validity checking techniques triangulation techniques.The results of the solution research did not occur in default in granting bank guarantees, in addition to following banking regulations in issuing bank guarantees, the 6C policy of bank guarantee applicants. This process is not enough because in practice there are still many defaults. Bankers and banking human resources need to improve their scientific abilities, and expertise in the fields of accounting, law, and economic politics, as individuals who are moral, ethical and have good character, have a professional mindset, and can work well in teams. On the part of the applicant for the bank guarantee, it must be based on good intentions, bound by a legal agreement as evidence in the event of default in the future.